Scientific Advancement in Forecasting of Administrative and Legal Threats to the Security of Economic Entities - CHISTOKLETOV, Leontiy G.; SOPILNYK, Rostyslav L.; SOPILNYK, Lyubomyr I.; SHISHKO, Valeriy V.; KHITRA, Oleksandra L. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).12, 2019)
The article is devoted to the problems of forecasting administrative and legal threats to the security of economic entities as a separate field of scientific research. The attention is focused on the essence and features of legal forecasting, the characters of the cause of administrative and legal threats to the security of economic entities and their essence. On the basis of the analysis of the most famous nowadays proposals concerning the phases of legal forecasting, the model of the stage of forecasting of administrative and legal threats to the security of economic entities is proposed. It was noted that the resolution of the above problem in Ukraine was not investigated sufficiently. That proves the relevance of the research direction and predetermines the need for further studies in this field.